2003
DOI: 10.1016/s0002-9440(10)64298-8
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic and Synaptic Pathology in Experimental Autoimmune Encephalomyelitis

Abstract: Evidence has shown that excitotoxicity may contribute to the loss of central nervous system axons and oligodendrocytes in multiple sclerosis and experimental autoimmune encephalomyelitis (EAE). Because dendrites and synapses are vulnerable to excitotoxicity, we examined these structures in acute and chronic models of EAE. Immunostaining for microtubule-associated protein-2 showed that extensive dendritic beading occurred in the white matter of the lumbosacral spinal cord (LSSC) during acute EAE episodes and EA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
1
6

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 62 publications
(69 reference statements)
6
75
1
6
Order By: Relevance
“…29 At the histological level, neuronal injury detected by dendritic beading was observed in Lewis rats immunized with MBP. 30 Finally, at the electrophysiological level, motor and sensory transmission defects in SJ/L mice corresponded with the appearance of neurological deficits and occurred in both the inflammatory period of the acute attack as well as in the chronic demyelinating stages. 31 This study indicated that defects in synaptic function, and not solely demyelination, resulted in clinical symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…29 At the histological level, neuronal injury detected by dendritic beading was observed in Lewis rats immunized with MBP. 30 Finally, at the electrophysiological level, motor and sensory transmission defects in SJ/L mice corresponded with the appearance of neurological deficits and occurred in both the inflammatory period of the acute attack as well as in the chronic demyelinating stages. 31 This study indicated that defects in synaptic function, and not solely demyelination, resulted in clinical symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Positive effects on remyelination and also neuroprotection are obtained by T4 administration in DA rats affected by EAE. This is a model of chronic relapsing-remitting EAE, which is characterized by extensive demyelination (35) and axonal, dendritic, and synaptic damage (36). When administered during the acute phase of the disease, T4 favors lineage toward oligodendrocytes, as indicated by increased expression of the OPC marker PDGF␣R, increases expression of MBP, and favors myelin sheath reorganization, which returns to a thickness comparable to that in control rats.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PMCAs are localized to both synaptic terminals and dendrites (21). Thus, a reduction in PMCA activity may damage not only axons but also dendrites, which are affected during EAE (44). Indeed, it has been suggested that dendritic arborization of Purkinje cells in PMCA2 null mice is reduced as compared with their wild-type littermates (23).…”
Section: Discussionmentioning
confidence: 99%